Clostridioides difficile spores stimulate inflammatory cytokine responses and induce cytotoxicity in macrophages. (August 2021) - Chiu, Po-Jung; Rathod, Jagat; Hong, Yu-Ping; Tsai, Pei-Jane; Hung, Yuan-Pin; Ko, Wen-Chien; Chen, Jenn-Wei; Paredes-Sabja, Daniel; Huang, I-Hsiu
Abstract: Clostridioides difficile is a gram-positive, spore-forming anaerobic bacterium, and the leading cause of antibiotic-associated diarrhea worldwide. During C. difficile infection, spores germinate in the presence of bile acids into vegetative cells that subsequently colonize the large intestine and produce toxins. In this study, we demonstrated that C. difficile spores can universally adhere to, and be phagocytosed by, murine macrophages. Only spores from toxigenic strains were able to significantly stimulate the production of inflammatory cytokines by macrophages and subsequently induce significant cytotoxicity. Spores from the isogenic TcdA and TcdB double mutant induced significantly lower inflammatory cytokines and cytotoxicity in macrophages, and these activities were restored by pre-exposure of the spores to either toxins. These findings suggest that during sporulation, spores might be coated with C. difficile toxins from the environment, which could affect C. difficile pathogenesis in vivo . Graphical abstract: Image 1 Highlights: C. difficile spores are universally readily phagocytosed by macrophages. Spores activate macrophages and stimulate inflammatory cytokine production. Toxins A and B-associated spores induced significant cytotoxicity in macrophages. C. difficile spores might be involved in triggering host immune responses in vivo .